Optimization and fabrication of curvilinear micro-grooved cutting tools for sustainable machining based on finite element modelling of the cutting process - Liu, Guoliang; Özel, Tuğrul; Li, Jianming; Wang, Dexiang; Sun, Shufeng (International journal of advanced manufacturing technology, 2020)
The benefits of micro-textures on cutting tools have been confirmed widely in implementing sustainable machining. However, the derivative cutting processes induced by the sharp edges of textures weakened the potential benefits. In our preliminary work, the newly designed curvilinear micro-grooved cutting tool has been proved to eliminate derivative cutting processes and implement sustainable machining than non-textured tools by three-dimensional (3D) finite element (FE) simulations. In this paper, the curvilinear micro-groove structures were optimized and fabricated to further improve the cutting performance of minimizing specific cutting energy. The results indicated that all the micro-groove parameters, including the width, spacing, depth, and edge distance (the distance from cutting edge to the micro-grooved area), showed obvious influence on specific cutting energy in their own ways. Specific cutting energy of the metal cutting processes can be effectively reduced by the optimal curvilinear micro-grooved cutting tools, although the optimal structures used in rough and finish turning conditions were different. In addition, a new two-step method was developed in this work to prepare curvilinear micro-grooves on carbide tools with femtosecond laser. The optimal curvilinear micro-grooved cutting tools were fabricated and used in cutting experiments, which verified the simulative results.